Eu sou feito no laboratório : uma reflexão sobre a bioarte e suas questões éticas através da produção de Eduardo Kac - Targa, Thaynã Silva (2018)
The present dissertation master's degree aims to discuss the way in which laboratory procedures currently existing in society impact the field of art. The art made in laboratories, called Bioarte, constitutes the central point of the proposed questioning.